2017
DOI: 10.24908/pceea.v0i0.6507
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers to Student Success: What Students Have to Say

Abstract: This paper focuses on feedback received from a set of qualitative questions that were administered to undergraduate students in the College of Engineering at the University of Saskatchewan, as part of a larger mixed methods study. The larger study aims to identify what characteristics, if any, can predict or are related to student success; The "start-stop-continue" method was utilized to assess student perceptions about their success in the college as a whole. The students were asked: Are there any specific th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Case Studies, Real-World Labs, Service Learning [26], [32], [15], [17], [28], [34], [31], [35] Course Delivery [26], [27], [29], [36], [37], [30], [33], [38], [39] Assessment [13], [16], [40], [41], [22], [42], [23], [43], [44] Theory Based or Survey Results [11], [45], [46], [47], [10], [19], [48], [1], [39], [49], [24], [25], [50], [51], [52] Out-of-class activities [53], [54], [55], [56], [57], [58] While there have been many successful interventions that improved student motivation discussed in the CEEA 2010-2018 proceedings, the relevant motivation theory behind each intervention is often missing. Understanding motivation theory may not be necessary ...…”
Section: Type Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case Studies, Real-World Labs, Service Learning [26], [32], [15], [17], [28], [34], [31], [35] Course Delivery [26], [27], [29], [36], [37], [30], [33], [38], [39] Assessment [13], [16], [40], [41], [22], [42], [23], [43], [44] Theory Based or Survey Results [11], [45], [46], [47], [10], [19], [48], [1], [39], [49], [24], [25], [50], [51], [52] Out-of-class activities [53], [54], [55], [56], [57], [58] While there have been many successful interventions that improved student motivation discussed in the CEEA 2010-2018 proceedings, the relevant motivation theory behind each intervention is often missing. Understanding motivation theory may not be necessary ...…”
Section: Type Of Interventionmentioning
confidence: 99%
“…Many engineering students were the top of their class in high school, and may not have been challenged academically, meaning they may have succeeded while relying on poor study strategies. They are often mentally and emotionally unprepared for engineering, which results in high levels of stress and anxiety, and reduced motivation [52].…”
Section: Motivation Theory and Introductory Technical Coursesmentioning
confidence: 99%
“…In Canada, some engineering students are beginning to react to the new transactional time expectations in different ways. Kuley, Maw, and Fonstad found that "Students felt that there was barely enough time to do the assignments each week, and that the heavy workload was not conducive to better learning" [7]. Other engineering educators are finding that students are now becoming "more strategic learners, valuing grades over learning," which may be related to the transactional nature of the student's time [8].…”
Section: Introductionmentioning
confidence: 99%
“…The feelings of lack of time and overburden of work seem to be true across the field of engineering education. Kuley et al noted that students are "not asking for easier work, but rather to have enough time to better grasp the concepts" [7]. Studies have noted poor time management in engineering students, and have linked time management and self-regulated learning to personal traits, characteristics, and success.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the problem is even more acute in technological disciplines as forms of engineering information (patents, standards, technical reports, conference proceedings, etc.) are less likely to have been addressed in secondary school STEM curriculum [8,12,10] leaving first-year engineering students at a disadvantage. The steep slope of skill development these students need to climb before making design decisions grounded in evidence has been understood as a key barrier to student success [9,10].…”
Section: Introductionmentioning
confidence: 99%